The Legal Framework for Women Grave Violations Protection During Armed Conflicts under The International Criminal Court - Alzaqibh, Ahmad Aqeil Mohammad; Alta’ani, Diala Ali; Al-Shawabkeh, Ibrahim; Al Qudah, Mouaid (Journal of Posthumanism, 2025)
The protection of women caught up in armed conflicts is a topic of considerable importance within international law, given that women are among the most vulnerable groups of people. In the process of codifying the rules of international law, the protection of women was strengthened in many international conventions. This protection was in the form of general protection for them because they are unarmed civilians and a special protection owing to their feminine nature. Therefore, this study aimed to explore the legal protection for women from grave violations during armed conflicts within the framework of the Statute of the International Criminal Court (ICC). Results revealed that the ICC has established an international criminal justice system for protecting women against violence, whether they are civilians, prisoners of war, or detainees. Furthermore, the ICC considered all forms of violence against women of a gravity equivalent to crimes against humanity. In addition, women enjoy general protection under the principle of complementarity between the ICC and states and through the establishment of individual and collective accountability for violations against women. However, the Statute of the ICC has some shortcomings in protecting women, including: (1) the need to introduce laws that establish the international criminal responsibility of legal persons; (2) the absence of an explicit provision on the issues of statutory limitations and amnesty for crimes against women; and (3) the existence of an impediment to the work of the ICC resulting from the power granted to the Security Council to suspend the ICC proceedings if they threaten international peace.